Classification and Frequency of Crown Whirlpool Patterns in Male Hair Transplant Patients - Kamal Uddin Khan, Farzana Abdullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Many males around the world struggle with androgenetic alopecia, more often known as male pattern baldness. Hair in the crown area of the scalp tends to arrange itself into spirals or swirls when seen from above. Although crown whorl patterns in male hair transplant patients are important, there is only limited information about them. Materials and Methods: A cross-sectional study was conducted from June 2022 to January 2023. All male patients, aged between 20 and 65, getting hair transplants were part of the study. A scalp exam and preoperative photos were done to determine if the head has a singular, double or indetectable whorl pattern. Results: Three main groups for the crown hair whirlpool were found: single 29 patients (58%), dual 3 patients (6%) and undetectable 18 patients (36%). The site where most single whirlpools (90% of cases) were observed was the central position, while dual and variant patterns were found in the parietal and right/left parietal areas making single pattern more prevalent with central position when compared to other with chi-square p-value of 0.002. Conclusion: Preoperative scalp mapping, personalized surgery and thought about hair patterns support improved results for patients. Knowing the differences in hair whorl patterns for men supports the development of better hair restoration methods and increases patient happiness. Keywords: crown whirlpool, hair transplant, pattern baldness, personalized surgery.